(untitled) (Revista Educação, Artes e Inclusão, 2023)
Theoretical investigation from a bibliographic and qualitative perspective, which sought to understand and problematize the discourses produced on inclusion in the context of research published in the 18th and 19th National Meeting of Teaching Chemistry (ENEQ) addressing experimental activities. In the analysis undertaken, it was possible to perceive that the dialogues between experimentation and inclusion bring ideas that cause misunderstandings, generate doubts and signal thoughts of uncertainty. However, it was also realized how much the experimental activities need to be problematized in the various contexts that go through the Teaching of Chemistry. Experimental practices need to be reframed, to break barriers on the beliefs that solidify the discourse of the experiment that foresees results that have not even been built yet. It is understood that the experimental activities need to be interpreted as didactic actions that contribute to the construction of chemical knowledge of social and cultural relevance for the coexistence of male and female students in our schools, considering that this can be a connection between understanding the inclusion and Chemistry Teaching.